First record of the genus Sundagrapha Holloway, 1982 (Lepidoptera, Geometridae, Ennominae, Cassymini) from China, with description of a new species - Liu, Bo; Yan, Wei (Zootaxa, 2025)
The genus Sundagrapha Holloway, 1982 is reported from China for the first time. A new species, Sundagrapha recta sp. nov., is described from Hainan Province. Adults of both sexes and their genitalia are illustrated and compared with those of closely related species. Additionally, a comprehensive identification key for all currently known species of Sundagrapha is provided.